The Goldbergs. the complete sixth season. [videorecording (DVD)] - McLendon-Covey, Wendi, 1969-; Giambrone, Sean, 1999-; Gentile, Troy; Orrantia, Hayley, 1994-; Segal, George; Garlin, Jeff, 1962-; Oswalt, Patton, 1969- (Sony Pictures Home Entertainment, 2019)
Adam Goldberg continues navigating high school while his mom, Beverly, continues bedazzling her way through life and his dad, Murray, parents from the comfort of his recliner in his underpants.